1999
DOI: 10.1016/s0896-6273(00)81029-6
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Synaptic Activity in Intact Brain and Slices with FM1-43 in C. elegans, Lamprey, and Rat

Abstract: The fluorescent probe FM1-43 has been used extensively for imaging vesicle recycling; however, high nonspecific adsorption resulting in elevated background levels has precluded its use in certain tissues, notably brain slices. We have found that a sulfobutylated derivative of beta-cyclodextrin (ADVASEP-7) has a higher affinity for FM1-43 than the plasma membrane. ADVASEP-7 was used as a carrier to remove FM1-43 nonspecifically bound to the outer leaflet of the plasma membrane or extracellular molecules, signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
127
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 23 publications
0
127
0
1
Order By: Relevance
“…Mechanisms underlying the interaction of FM2-10 with the guinea pig cough receptor Unlike styryl dye labeling of other cells (Betz et al, 1992;Ryan et al, 1993;Ribchester et al, 1994;Kirchgessner et al, 1996;Hay and Hasser, 1998;Kay et al, 1999;Gale et al, 2001) we found that FM2-10 staining of cough receptors did not require and was not reversed by nerve stimulation. Although labeling was prevented by cooling (suggesting an active process), it was unaffected by removing extracellular calcium, arguing against calciumdependent vesicular transport.…”
Section: Discussionmentioning
confidence: 50%
“…Mechanisms underlying the interaction of FM2-10 with the guinea pig cough receptor Unlike styryl dye labeling of other cells (Betz et al, 1992;Ryan et al, 1993;Ribchester et al, 1994;Kirchgessner et al, 1996;Hay and Hasser, 1998;Kay et al, 1999;Gale et al, 2001) we found that FM2-10 staining of cough receptors did not require and was not reversed by nerve stimulation. Although labeling was prevented by cooling (suggesting an active process), it was unaffected by removing extracellular calcium, arguing against calciumdependent vesicular transport.…”
Section: Discussionmentioning
confidence: 50%
“…Indeed, various markers have been used, such as sulforhodamine (Lichtman et al 1985), fluorescently labeled antibodies (Kraszewski et al 1996;Westphal et al 2008), styryl dyes (i.e., FM dyes; Betz and Bewick 1992), and fluorescent dextrans (Holt et al 2003). Among these markers, FM dyes have proved to be valuable in a number of different preparations, including neuromuscular junctions (NMJ) from the frog (Betz and Bewick 1992), snake (Teng et al 1999), lizard (Lindgren et al 1997), and larval Drosophila (Ramaswami et al 1994); hippocampal neurons in culture (Ryan et al 1993) and acute slice (Zakharenko et al 2001); goldfish retinal bipolar cells (Zenisek et al 2000); Caenorhabditis elegans neurons (Kay et al 1999); rat calyx of Held (de Lange et al 2003); inner and outer hair cells (Griesinger et al 2002;Kaneko et al 2006); and a variety of nonneuronal preparations (for a review, see Cochilla et al 1999). …”
Section: Discussionmentioning
confidence: 99%
“…Another approach to improve the image quality has been to increase the amount of dye that is washed out of the preparation by including the oligosaccharide ADVASEP-7 during the washing steps. ADVASEP-7, which is a derivative of β-cyclodextrin, has a higher affinity for FM dyes than do biological membranes (Kay et al 1999). The addition of ADVASEP-7 to washing solutions greatly reduces background staining, making it possible to image systems such as rat brain and C. elegans slices.…”
Section: Slice Preparationsmentioning
confidence: 99%
“…Active synapses were labeled with a 2 min application of 10 M FM1-43FX [fixable version of N-(3-triethylammoniumpropyl)-4-(4-(dibutylamino)styryl) pyridinium dibromide] (Invitrogen, Eugene, OR) and 45 mM K ϩ (equimolar substitution for Na ϩ ) in extracellular recording saline containing the following (in mM): 138 NaCl, 4 KCl, 2CaCl 2 , 1 MgCl 2 , 10 glucose, 10 HEPES, and 0.025 D-APV, and 0.001 NBQX, pH 7.25. Cultures were washed for 10 s with extracellular recording saline containing 500 M Advasep-7 (CyDex, Overland Park, KS) to remove nonspecific dye (Kay et al, 1999) and washed in saline alone for 10 min. Cultures were fixed in 4% paraformaldehyde/0.2% glutaraldehyde in PBS for 10 min.…”
Section: Methodsmentioning
confidence: 99%